Experimental investigation of the extreme seeking control on a transcritical CO2 heat pump water heater. (January 2022) - Cui, Ce; Zong, Shuo; Song, Yulong; Yin, Xiang; Cao, Feng
Highlights: Model-free real-time maximization of transcritical system COP. ESC design for optimizing the CO2 discharge pressure. Experimental investigation of ESC control under various conditions. The system COP was maximumly improved by 8.81% under the ESC control. Abstract: In recent years, CO2 has been widely considered as one of the most promising substitutes for the HFCs due to the consideration of both the environmental protection and high efficiency. However, the system performance of a transcritical CO2 cycle is greatly influenced by the discharge pressure, the determination of which has been the most important and hottest issue. Apart from the traditional correlation development through theoretical analysis and experimental data, model-free extreme seeking control method has also been proved to be effective through the simulation investigation in literatures. However, the related experimental investigation is still rare. In this article, we provide the experimental investigation of the ESC method on a transcritical CO2 heat pump water heater. The ESC controller was designed based on the system dynamics and then implemented on the test rig. Experimental investigation was then carried out under the fixed design condition (inlet water temperature at 40°C and air temperature at 0°C) and the fixed off-design condition (inlet water temperature at 45°C and air temperature at 0°C), the system COP operated by the ESC controller was improved by 7.62% after 4167s, and by 8.81% after 4287s respectively. The experimental results under the continuous step change of the inlet water temperature (40-45-40°C) demonstrated the repeatability and the effectiveness of the ESC control under changing working conditions. The static performance of the heat pump water heater was finally explored under the inlet water temperatures of 40°C and 45°C to furtherly demonstrate that the found discharge pressures of the ESC controller were indeed the optimal discharge pressures of the transcritical CO2 heat pump.